SME policy and firms' productivity in Latin America - Pablo Ibarrarán; Alessandro Maffioli; Rodolfo Stucchi (Institute for the Study of Labor (IZA), 2009)
Very little is known about the effectiveness of SME policies, and a careful look at the structure, mechanisms and incentives provided by these policies suggest caution in their implementation and, most importantly, the need to carefully and closely monitor their results. This paper relies on the microeconometric analysis of a homogeneous dataset of sixteen Latin American and Caribbean countries to analyze the magnitude and determinants of the productivity gap between large and SME firms and to simulate of the impact on productivity of various policy scenarios.
urn:nbn:de:101:1-2009102669
Keywords: D24; L53; L60; O38; O54; 330; SMEs; SME policy; productivity; Latin America; Klein- und Mittelunternehmen; Wirtschaftsförderung; Produktivität; Wirkungsanalyse; Lateinamerika